Arbuscular mycorrhizal fungi (AMF) species and abundance exhibit different effects on saline-alkaline tolerance in Leymus chinensis. Issue 1 (1st January 2020) - Cao, Yaping; Wu, Xuefeng; Zhukova, Anastasiia; Tang, Zhanhui; Weng, Yue; Li, Zhenxin; Yang, Yurong
ABSTRACT : Arbuscular mycorrhizal fungi (AMF) was considered as a biotechnological tool for plant stress tolerance improvement and degraded ecosystem restoration. However, the variations in the effects of AMF species and abundance on plant performance under stress condition have to be still investigated. The study was conducted to evaluate the mechanisms of five AMF species, single or mixture, on Leymus chinensis stress tolerance along a saline-alkaline gradient. The results showed that AMF enhanced plant stress tolerance by promoting plant growth, enhancing nutrient absorption, maintaining ion balance, and improving photosynthetic efficiency. Funneliformis mosseae, Rhizophagus intraradices and the mixture treatments had more beneficial effects than Diversispora versiformis and Acaulospora scrobiculata inoculations. Plant grown under high stress level exhibited more benefits from AMF symbiosis. Our study suggests that not only presence of AMF, but also the species and abundance should be considered to reveal the exact effects of AMF on plant saline-alkaline tolerance and degraded grassland restoration.